2019
DOI: 10.1111/deci.12365
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Optimal Model of Pricing, Rebate Value, and Redemption Hassle

Abstract: Although rebates are widely employed, redemption is not effort free, and the hassle of redemption is an important decision variable for buyers. The current research examines the impact of hassle cost on optimal rebate strategy. An analytical model is developed that simultaneously determines the supply chain's optimal price, level of rebate value, and rebate‐redemption hassle, while allowing for slippage (as consumers may forget to redeem a rebate), in both a centralized and decentralized supply chain. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Fogel and Thornton found that too much hassle discourages consumers from using rebates, while too little hassle induces all customers to use rebates [27]. Popkowski et al examined the effect of hassle costs on optimal rebate strategies and showed that the hassle of rebates level plays a key role in dividing the market into rebate and non-rebate purchasers [44].…”
Section: Research On Consumer Buying Behaviormentioning
confidence: 99%
“…Fogel and Thornton found that too much hassle discourages consumers from using rebates, while too little hassle induces all customers to use rebates [27]. Popkowski et al examined the effect of hassle costs on optimal rebate strategies and showed that the hassle of rebates level plays a key role in dividing the market into rebate and non-rebate purchasers [44].…”
Section: Research On Consumer Buying Behaviormentioning
confidence: 99%
“…Analogously, we find that delayed discounts can increase profits, but in a different setting—we require neither inconvenience costs nor postpurchase changes to utility, and we permit repeat purchasing. In a recent paper, Zhang, Popkowski Leszczyc, Qu, and Joseph (2019) relate redemption costs to rebates' profitability in centralized and decentralized supply‐chain settings, and show that decentralization leads to larger optimal rebates. Based on an empirical study, Zhang, Krishna, and Dhar (2000) present evidence that up‐front discounts tend to increase sales, yet “from a profitability perspective, rear‐loaded promotions may be better than front‐loaded promotions.” Our analytical results agree with their empirical finding, given that postsale credit is a form of rear‐loaded promotion.…”
Section: Literature Reviewmentioning
confidence: 99%